Perbandingan Perbankan Konvensional Dan Syariah (Studi Mengenai Perbedaan) - Muhammad Irsyad (Iuris Studia: Jurnal Kajian Hukum, 2023)
Islamic banks are financial institutions that have an exclusive mission (risalah) and methodology (manhaj), namely the Shariah framework and its principles originating from the ethics and values of Islamic Sharia which are comprehensive and universal. In channeling funds, Islamic banks apply several contracts, including: murabaha, salam, istishna', ijarah, mudrabah and musyarakah. In service activities, Islamic banks also apply several contracts, including: kafalah (bank guarantee), hawalah (debt transfer), sharf (forex buying and selling), wakalah. Indonesia already has sufficient legal instruments governing Islamic banking, including the Law No. 10 of 1998 concerning Banking, Law no. 23 of 1999 concerning Bank Indonesia, Law no. 3 of 2006 as amended by Law no. 50 of 2009 concerning the Religious Courts and finally with the issuance of Law No. 1 21 of 2008 concerning Islamic Banking. The study of the differences between Islamic and conventional banks is not a new study anymore, but in this case, according to the authors of the study, it still requires more attention, because today's society still equates Islamic banks with conventional banks, which in reality are very different. The difference between Islamic banks and conventional banks when viewed in terms of understanding. Islamic banks are banks that practice their business activities based on sharia principles which in principle do not contain elements of usury, maysir, gharar, unjust and unlawful objects. In contrast to conventional banks which are banks that practice conventional business activities, which in their activities provide services in the past Cross payments are based on procedures and conditions that have been stipulated by law. However, in Islamic banks there are principles of sharia that do not exist in conventional banks. The function of Islamic banks is wider than conventional banks. Even though they work together to collect and distribute community funds.